Thyroid autoimmunity and vitamin D: Effects on in vitro fertilization/intracytoplasmic sperm injection laboratory outcomes - Liu, Yalong; He, Zining; Huang, Ning; Zeng, Lin; Meng, Fangyin; Li, Rong; Chi, Hongbin (Frontiers in Endocrinology, 2022)
This prospective cohort study aimed to determine the effects of thyroid autoimmunity, serum/follicular fluid vitamin D levels, and vitamin D receptor expression in granulosa cells on laboratory outcomes of in vitro fertilization/intracytoplasmic sperm injection. The study included 206 women with or without thyroid autoimmunity undergoing in vitro fertilization/intracytoplasmic sperm injection ovarian stimulation cycles. The primary outcomes in thyroid autoimmunity and non-thyroid autoimmunity patients with high or low follicular fluid vitamin D levels (high vitamin D level, ≥20 ng/mL; low vitamin D level, <20 ng/mL) were the number of oocytes retrieved and quality of embryos. The secondary outcomes were the association between serum and follicular fluid vitamin D levels and vitamin D receptor expression in granulosa cells. Our study revealed that thyroid autoimmunity was associated with fewer good-quality embryos but not oocytes (p = 0.010). The vitamin D level in the follicular fluid was significantly correlated with that in the serum (p < 0.001, r > 0.5). The study populations in the thyroid autoimmunity and non-thyroid autoimmunity groups were divided into two subgroups based on high/low serum/follicular fluid vitamin D levels. There was no significant difference in the number of retrieved oocytes and good-quality embryos between the subgroups with high or low vitamin D levels (p > 0.05), and the incidence of thyroid autoimmunity was comparable between the subgroups (p > 0.05). Linear regression analysis indicated that thyroid autoimmunity had a negative effect on the number of healthy embryos (p = 0.038). Reverse transcription-polymerase chain reaction results indicated that vitamin D receptor expression in granulosa cells was positively correlated with follicular vitamin D levels in the thyroid autoimmunity (p = 0.0002) and non-thyroid autoimmunity (p < 0.0001) groups. The current findings suggest that thyroid autoimmunity may have a more detrimental effect on in vitro fertilization/intracytoplasmic sperm injection laboratory outcomes than vitamin D.